PENGARUH PEMBELAJARAN 5E LEARNING CYCLE BERBANTUAN MULTIMEDIA TERHADAP MINAT BELAJAR IPA - Prima Anugraheni (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
Abstract The purpose of this study was to determine the effect of learning cycle 5E assisted multimedia on student interest in science than learning cycle 5E without multimedia. Methods used are quasi experiment with the matching pretest posttest control group design. Subjects in this study were students of gradeVIII from SMPN 2 Ciseeng Kabupaten Bogor. Data were collected using a questionnaire students' interest in science. Results from the study showed that learning cycle 5E assisted multimedia further increase student interest in science than learning cycle 5E without multimedia (α = 0.05) with an average increase of interest in science for the multimedia assisted by N-Gain indicated by 36, 94% and 17.45% without multimedia. Keywords: learning cycle 5E, multimedia, students interest in science Abstrak Tujuan penelitian ini adalah untuk mengetahui pengaruh pembelajaran 5E learning cycle berbantuan multimedia terhadap minat belajar siswa dibandingkan dengan pembelajaran 5E learning cycle tanpa multimedia. Metode penelitian yang digunakan adalah kuasi eksperimen, dengan desain the matching pretest posttest control group design. Subjek dalam penelitian ini adalah siswa-siswi kelas VIII SMPN 2 Ciseeng Kabupaten Bogor. Data dikumpulkan menggunakan angket minat belajar IPA siswa. Hasil dari penelitian menunjukkan bahwa pembelajaran 5E learning cycle berbantuan multimedia lebih meningkatkan minat belajar IPA siswa dibandingkan dengan pembelajaran 5E learning cycle tanpa multimedia (α = 0,05) dengan rata-rata peningkatan minat belajar IPA untuk yang berbantuan multimedia ditunjukkan dengan N-Gain sebesar 36,94% dan tanpa multimedia sebesar 17,45%. Kata Kunci: 5E learning cycle, multimedia, minat belajar IPA Permalink/DOI: http://dx.doi.org/10.15408/es.v9i1.1722